Pengaruh Model Problem Based Learning Terhadap Kemampuan Berpikir Kreatif Peserta Didik Dalam Memahami Pembelajaran Matematika Kelas V SDN 33 Palembang - Shinta Wulandari; Misdalina Misdalina; Tanzimah Tanzimah (Departement of Mathematics Education, 2023)
This study aims to determine the influence of the problem-based learning model on the creative thinking ability of students in understanding mathematics learning grade V SDN 33 Palembang. The research method used is quantitative type of experiment with the form of true experimental design and posttest only control design. The population in this study amounted to 112 students consisting of class V A which amounted to 29 students as an experimental class, V B which amounted to 28 students as a control class, V C which amounted to 27 students, and V D which amounted to 28 students. The sample in this study used a simple random sampling technique. Data collection techniques using tests and documentation. Data analysis techniques use t tests (independent sample t test). From the results of research data processing with the help of the SPSS application, a value of tcount = 5.112 and a value of ttable = 1.673 with α = 0.05 and df = 55, then 5.112 ≥ 1.673 thus tcount ≥ ttable. In accordance with the prerequisites of the hypothesis test, the H0 is rejected and Ha accepted. This shows that there is an influence of the problem-based learning model on the creative thinking ability of students in understanding grade V mathematics learning at SDN 33 Palembang.